CONCEPTUAL CORRESPONDENCE THROUGH MENTAL SPACE IN CREATING WORDS AT THE NOVEL HARRY POTTER AND THE SORCERERS STONE - Ariyani Pedo, Venansia Ajeng Surya (Eduscience : Jurnal Ilmu Pendidikan, 2019)
AbstractThe aim of the research was to find out the process of conceptual correspondence of the mental space J. K. Rowling has when producing new words in "Harry Potter and the Sorcerers stone. The research applied a qualitative descriptive method by using the productivity and creativity theory by Aronoff&Fudeman and Kridalaksana,  the mental space theory by Saeed,  and the theory of conceptual correspondence by Lee. The observation was applied by focusing on the words in Chapter I  III. Analysis was done by applying the theory of David Lee (2001) concerning conceptual correspondence of the mental space. The results indicate that there are 7 new words and phrases as the result of J. K. Rowlingcreativity. The aspects found can be influenced by the physical environment such as the nature and location as well as the linguistic aspects such as the derivation process, purpose of use, and meaning.  Keywords: productivity, creativity, mental space AbstrakTujuan penelitian ini yaitu mengetahui korespondensi konseptual ruang mental yang dimiliki J. K. Rowling saat memproduksi kata-kata baru dalam â€œHarry Potter and the Sorcerer Stone. Penelitian ini menerapkan metode kualitatif deskriptif dengan mengaplikasikan teori produktivitas dan kreativitas yang diusung oleh Aronoff & Fudeman dan Kridalaksana, teori ruang mental oleh Saeed dan teori korespondensi konseptual oleh Lee.  Metode simak diaplikasikan dengan berfokus pada analisis bab I dan III dari novel tersebut. Analisis dilakukan dengan menerapkan teori David Lee (2001) yang  berkaitan dengan korespondensi konseptual ruang mental.Â  Hasil penelitian menunjukkan bahwa terdapat 7 kata dan frasa baru sebagai wujud kreativitas dari J. K. Rowling. Unsur-unsur yang muncul pada korespondensi konseptual dapat dipengaruhi oleh lingkungan fisik seperti sifat dan lokasi serta juga dari aspek linguistik seperti proses derivasi, tujuan penggunaan dan makna yang menyertai. Kata kunci: produktivitas, kreativitas, ruang mental